The Tobacco Control Scale: a new scale to measure country activity. Issue 3 (25th May 2006) - Joossens, L; Raw, M
Abstract : Objectives: To quantify the implementation of tobacco control policies at country level using a new Tobacco Control Scale and to report initial results using the scale. Method: A questionnaire sent to correspondents in 30 European countries, using a scoring system designed with the help of a panel of international tobacco control experts. Results: The 30 countries are ranked by their total score on the scale out of a maximum possible score of 100. Only four countries (Ireland, United Kingdom, Norway, Iceland) scored 70 or more, with an eight point gap (most differences in scores are small) to the fifth country, Malta, on 62. Only 13 countries scored above 50, 11 of them from the European Union (EU), and the second largest points gap occurs between Denmark on 45 and Portugal on 39, splitting the table into three groups: 70 and above, 45 to 62, 39 and below. Ireland had the highest overall score, 74 out of 100, and Luxembourg was bottom with 26 points. However even Ireland, much praised for their ban on smoking in public places, did not increase tobacco taxes in 2005, for the first time since 1995. Conclusions: Although the Tobacco Control Scale has limitations, this is the first time such a scale has been developed and applied to so many countries. We hope it will be useful in encouraging countries to strengthen currently weak areas of their tobacco control policy.